2009
DOI: 10.5551/jat.e602
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness in Patients with Non-Diabetic Chronic Kidney Disease (CKD)

Abstract: Background: Patients with chronic kidney disease (CKD) have a high prevalence of cardiovascular disease (CVD). Arterial stiffness plays an important role in the pathogenesis of CVD; however, to date, there have been no reports of the assessment of arterial stiffness in patients at different stages of non-diabetic CKD. Methods: We studied 50 patients with non-diabetic CKD (stages 1 − 5, 5D) receiving medical treatment at Tokyo Women's Medical University. Pulse wave velocity (PWV) was assessed using an applanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…39,40 Similar correlation was identified between PWV with age, eGFR, CSBP, CPP were found in our results consistent with these previous studies. Wang et al 41 showed that SBP, eGFR were the major determinants of arterial stiffness.…”
Section: Discussionsupporting
confidence: 92%
“…39,40 Similar correlation was identified between PWV with age, eGFR, CSBP, CPP were found in our results consistent with these previous studies. Wang et al 41 showed that SBP, eGFR were the major determinants of arterial stiffness.…”
Section: Discussionsupporting
confidence: 92%
“…A growing body of evidence has been accumulated that CKD constitutes a critical determinant of 19) . This clinically important issue has been focused on intensively because of the recently wellrecognized topic, i.e., cardio-renal continuum 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Details of the methodology have been described elswhere 10) . Occlusion and monitoring cuffs were placed snugly around all four limbs with the patient in the supine position, and the pressure waveforms of the brachial and tibial arteries were recorded with an automatic waveform analyzer after 15 min of bed rest.…”
Section: Measurement Of Pwvmentioning
confidence: 99%